Giant Polypoid Tumor Expressing on the Pyloric Ring. (22nd January 2015) - Sonoda, Hirofumi; Kobayashi, Takashi; Endo, Yuhei; Irie, Shoichi; Hirata, Toru; Minamimura, Keisuke; Mafune, Ken-ichi; Mori, Masaya
Abstract : A 66-year-old Japanese man was referred to our hospital because of suspected duodenal cancer. Upper gastric endoscopy revealed a giant polypoid-type tumor that extended from the duodenum bulb to the pyloric ring. A computed tomography scan revealed a slightly enhanced lobular tumor protruding into the duodenum bulb. Positron emission tomography showed an accumulation of 18 F-fluorodeoxyglucose in the area extending from the antrum of the stomach to the duodenum bulb. Since an endoscopic ultrasound test suggested that the tumor might invade the muscular tunic, indications of endoscopic mucosal resection were not favored, and the tumor was curatively removed via distal gastrectomy. The histopathologic diagnosis was papillary adenocarcinoma, and the invasion depth was the mucosal layer without vascular invasion, which was different from the preoperative diagnosis. Our case suggests the difficulties in precise diagnosis of the invasion depth of the giant polypoid cancer.